Purification and Properties of Polygalacturonase Produced by Thermophilic Fungus Thermoascus aurantiacus CBMAI-756 on Solid-State Fermentation. (12th September 2013) - Martins, Eduardo da Silva; Leite, Rodrigo Simões Ribeiro; da Silva, Roberto; Gomes, Eleni
Abstract : Polygalacturonases are enzymes involved in the degradation of pectic substances, being extensively used in food industries, textile processing, degumming of plant rough fibres, and treatment of pectic wastewaters. Polygalacturonase (PG) production by thermophilic fungus Thermoascus aurantiacus on solid-state fermentation was carried out in culture media containing sugar cane bagasse and orange bagasse in proportions of 30% and 70% (w/w) at 45°C for 4 days. PG obtained was purified by gel filtration and ion-exchange chromatography. The highest activity was found between pH 4.5 and 5.5, and the enzyme preserved more than 80% of its activity at pH values between 5.0 and 6.5. At pH values between 3.0 and 4.5, PG retained about 73% of the original activity, whereas at pH 10.0 it remained around 44%. The optimum temperature was 60–65°C. The enzyme was completely stable when incubated for 1 hour at 50°C. At 55°C and 60°C, the activity decreased 55% and 90%, respectively. The apparent molecular weight was 29.3 kDa, K m of 1.58 mg/mL andV max of 1553.1 μ mol/min/mg. The presence of Zn +2, Mn +2, and Hg +2 inhibited 59%, 77%, and 100% of enzyme activity, respectively. The hydrolysis product suggests that polygalacturonase was shown to be an endo/exoenzyme.